Social Capital and Crises with an Application to Iceland - Thorvaldur Gylfason (Center for Economic Studies and ifo Institute (CESifo), 2015)
Economic growth is propelled in part by the accumulation of different kinds of capital, including social capital in its several guises. This paper considers the interplay between financial crises and various aspects of social capital which, if it is allowed to depreciate, can undermine economic prosperity and growth and possibly also contribute to crises. Specifically, the paper offers some empirical comparisons between the experience of the United States in the 1920s and in the 1990s until 2008 with the experience of Sweden and Iceland. The working hypothesis is that social capital decay can be a precursor as well as consequence of slow economic growth and of financial crises. Iceland is a case in point. An increasingly unfair distribution of income and wealth is likely to exacerbate the problem.
Keywords: D63; D73; G01; 330; social capital; inequality; corruption; trust; financial crises